The Influence Of Perceptions Of Benefits, Trust, And Risks On The Use Of Qris By Msmes In Purwokerto - Feogeok, Sari; Pramuka, Bambang Agus; Putri, Negina Kencono; Budiarti, Laeli (Jurnal sosial dan sains, 2025)
MSMEs as one of the pillars of the economy in Indonesia must not be left behind by rapidly advancing technology, MSMEs must be able to compete in this era of globalization. The government is collaborating with the payment system industry to develop the QRIS application and it is hoped that MSME players will use QRIS in their business activities. This research aims to determine and analyze the influence of perceived benefits, trust, and risks on the use of QRIS by MSMEs in Purwokerto. The subjects of this research were 80 MSMEs in the food and beverage sector. Data analysis uses multiple linear regression. The results of the research conclude that perceived benefits, trust, and risks simultaneously and partially have a significant effect on the use of QRIS by MSMEs in Purwokerto